Teaching materials based on sinau digital unesa: can it improve students' swimming knowledge? - Rudi Rudi; Andi Mariono; Alim Sumarno; Bayu Budi Prakoso; Priya Yoga Pradana (Universitas Sriwijaya, 2025)
Research Problems: The only way to master swimming skills is to practice dominated by practice. As a result, the duration of practice in swimming courses takes up time to learn theory. The development of teaching materials based on the Learning Management System (LMS) is the right choice for assisting students in practising practice. Research Objectives: This development research aims to test the effectiveness of using LMS-based teaching materials called sinau digital unesa to improve students' knowledge of swimming material. Methods: The ADDIE development model was completed at each stage. Testing of the development results was carried out on 97 first-semester students who took swimming courses. The feasibility of the development product was validated by material experts and learning media. The implementation of teaching materials was tested for effectiveness using a one-group pretest-post-test design. The research instrument used a knowledge test. Data analysis used descriptive statistics and t-tests. Results: The product feasibility test by experts on the development results showed that the feasibility value of the lecture plan (RPS) was 95% (very feasible), the learning content was 95% (very feasible), the media in the LMS was 95% (very feasible), and the LMS teaching materials based on the material were 94.4% (very feasible). The results of the implementation of the development product show that the results of the development of teaching materials can significantly increase student knowledge (t = 3.19, p = 0.002) by 6.54%. Conclusion: It is concluded that LMS-based teaching materials can help students improve their knowledge of swimming material.